Dry Sliding Wear Behavior of Chemically Treated Sisal Fiber Reinforced Epoxy Composites - Behera S.; Gautam R.K.; Mohan S.; Chattopadhyay A. (My University, 2025)
The effect of fiber surface treatment on the structural, thermal, and tribological properties of sisal fibers and their epoxy composites were investigated in this research work. Sisal fibers were modified with alkali (NaOH), glutamic acid, and a combination of both alkali and glutamic acid. To analyze the effect of chemical modification on the properties of sisal fibers, scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-Ray diffraction (XRD), and thermogravimetric analysis (TGA) were performed. It is observed from the experimental results that there is an improvement in the surface roughness, crystallinity, and thermal stability of chemically treated fibers in comparison to untreated fibers. Microhardness properties of chemically treated sisal fiber reinforced epoxy composites (SFREC) also showed minor improvement. The dry sliding wear experiments were carried out according to Taguchi design of experiment (DOE) methods. The results of the wear test showed an increase in the wear resistance of chemically modified SFREC relative to untreated SFREC. The best wear properties were demonstrated by alkali treated SFREC. It is also observed from the findings of ANOVA that the applied load and sliding distance have the most defining effect on wear volume loss of SFREC. © 2021 Taylor & Francis.